Training in East Germany: An evaluation of the effects on employment and wages - Bernd Fitzenberger; Hedwig Prey (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1996)
Support of training has been one of the most important instruments of active labor market policy in East Germany. This paper attempts an evaluation of the effects of training on future employment and future wages of trainees. The analysis distinguishes between measures within and outside of the firm of the employee and whether the trainee receives public income maintenance. After describing the labor market developments in East Germany, we illustrate the evaluation problem. Then, we estimate a simultaneous model for participation in training, employment, and wages. Taking account of selection effects before participation, our findings mostly suggest positive effects of training on employment or wages. In this respect, public income support is only successful when training takes place in external institutions but not in the firm where the person is employed.
Keywords: J20; J60; C33; 330; East Germany; evaluation of training; employment probability; wage; selection bias; labor market policy; Berufsbildung; Wirkungsanalyse; Bildungsertrag; Arbeitsmarktpolitik; Neue Bundesländer